Between Involvement and Intervention: Perceptions, Difficulties and Parents’ Coping in the Distance Learning during the COVID-19 Pandemic - Zedan, Raed (Journal of Ethnic and Cultural Studies, 2024)
The outbreak of the COVID-19 Pandemic brought about a significant transformation in the education landscape, leading to the widespread adoption of distance education as the primary mode of learning. Due to legal restrictions imposed, students were unable to attend school and study in traditional settings such as classrooms. Instead, they had to remain at home with their parents, resulting in a greater need for parental involvement in their children’s education. This involvement took on diverse forms and held various meanings. The objectives of this study were to describe the attitudes and perceptions of parents towards distance learning and to examine the extent and nature of parental involvement. The research employed a mixed-method design, with 461 Arab and Jewish parents participating by completing a structured questionnaire, while an additional 139 parents took part in semi-structured interviews. The research findings revealed a prevalent negative attitude towards distance learning, as experienced during the COVID-19 period, with parents expressing dissatisfaction and disappointment regarding its implementation. While some parents reported a high degree of involvement, others chose not to be involved at all. The study also highlighted various challenges encountered by parents, including didactic-pedagogical, technological, economic, and other difficulties. Additionally, some parents exhibited interventionist behavior, disrupting Zoom classroom meetings by making comments, expressing reservations, or offering suggestions. On a positive note, a positive relationship was identified between parents’ involvement and their attitudes towards distance learning. The research findings have valuable implications for the education system, as they shed light on the attitudes, perceptions, and difficulties surrounding distance learning. These insights can help identify the barriers that hinder parental involvement in their children’s learning processes, thereby reducing its effectiveness. By understanding these challenges, the education system can strive to find methods and solutions to enhance the learning process for students and increase parental involvement.